Effect of Mindfulness-Based Stress Reduction on Anxious Thoughts of Wives of Veterans with Amputation - M. Zarnaghash; M. Mehrabizadeh Honarmand; K. Beshlideh; I. Davodi; S.A. Marashi (Afarand Scholarly Publishing Institute, 2019)
Aims: Amputation is the most disturbing and damaging thing a person may experience in his or her life. The aim of the present research was to investigate the effect of mindfulness-based stress reduction (MBSR) on anxious thoughts of wives of veterans with amputation. Materials and Methods: In this experimental study with pre-test post-test design with control group, 28 wives of veterans with amputation referring to veterans counseling center of Ahvaz were randomly chosen by available sampling method and they were assigned to experimental and control groups. The experimental group received 8 sessions of intervention based on MBSR. The instrument was the Wells's Anxious Thoughts Inventory scale, which was filled out by participants in pre-test and post-test stages. Data analysis was performed, using SPSS 20 software by multivariate covariance analysis and Bonferroni post hoc test. Finding: By controlling the effects of pre-test, there was a significant difference between the mean scores of the dimensions of the anxious thoughts in the experimental and control groups in the post-test (p<0.05). There was a significant difference between the mean scores of health worry (p<0.05) and meta-worry (p<0.0001) in the experimental and control groups, but there was no significant difference between the mean score of social worry in the experimental and control groups (p>0.05). Conclusion: Reducing MBSR decreases the anxious thoughts of wives of veterans with amputation.